Predicting Social Wariness in Middle Childhood: The Moderating Roles of Child Care History, Maternal Personality and Maternal Behavior - Degnan, Kathryn Amey (2008)
Children with behavioral inhibition, a temperamental style characterized by infant distress to novelty and childhood social reticence, exhibit both continuity and discontinuity of this behavioral trait over the course of development. However, few researchers have identified factors that might be responsible for these different patterns. In the current study, child care history, maternal personality and maternal behavior were examined as moderators of the relations between infant temperament, preschool social reticence and childhood social wariness. Seventy-seven children participated in this longitudinal study that began in infancy and continued into middle childhood. Maternal negative personality moderated the relation between infant temperament and 7-year social wariness. In addition, maternal behavior moderated the relation between preschool social reticence and 7-year social wariness. The findings suggest that a complex interplay of within-child and maternal factors affect the development of internalizing behavior in the early school years.